##### The minimal expression for the function &nbsp;...

The minimal expression for the function  F = A’B + AC + BC’D’ + BEF + BDF  will be

(A) (A+B)(B+C)(A’+C+D’+F)

(B) (A+B)(B+C)(A+C’+D+F’)

(C) (A+B)(B+C)(A’+C’+D+F)

(D) (A+B)(B+C)(A+C+D’+F)

Sumit Verma 24 Oct 2016 04:28 pm

F = A’B + AC + BC’D’ + BEF + BDF
AC + BC’D’ -> ABD’
F = A’B+AC+BC’D’+BEF+BDF+ABD’                     Consensus Theorem
A’B + ABD’ -> BD’
F = A’B+AC+BC’D’+BEF+BDF+ABD’+BD’            Consensus Theorem
F = A’B+AC+BD’(C+A+1)+BEF+BDF                    1st Distributive Rule
F = A’B+AC+BD’+BEF+BDF
F = B(A’+D’+EF+DF)+AC                                        1st Distributive Rule
F = B(A’+D’+F+EF)+AC                                           Absorption
F = B(A’+D’+F)+AC                                                  Absorption
F = (AC+B)(AC+A’+D’+F)                                        2nd Distributive Rule
F = (A+B)(C+B)(A+A’+D’+F)(C+A’+D’+F)               2nd Distributive Rule
F = (A+B)(C+B)(1+D’+F)(C+A’+D’+F)                     Complementarity
F = (A+B)(B+C)(A’+C+D’+F)

shivani 25 Oct 2016 11:28 am

sir how u got
// AC + BC’D’ -> ABD’

shivani 25 Oct 2016 11:29 am

i think minimal expression means SOP so y they have options of POS

Sumit Verma 25 Oct 2016 12:08 pm

@aantra No . Minimal expression can be either SOP or POS.